Advanced siRNA delivery in combating hepatitis B virus: mechanistic insights and recent updates - Linh Nguyen; Tiep Tien Nguyen; Ju-Yeon Kim; Jee-Heon Jeong (Journal of Nanobiotechnology)
Abstract Hepatitis B virus (HBV) infection is a major health problem, causing thousands of deaths each year worldwide. Although current medications can often inhibit viral replication and reduce the risk of liver carcinoma, several obstacles still hinder their effectiveness. These include viral resistance, prolonged treatment duration, and low efficacy in clearing viral antigens. To address these challenges in current HBV treatment, numerous approaches have been developed with remarkable success. Among these strategies, small-interfering RNA (siRNA) stands out as one of the most promising therapies for hepatitis B. However, naked siRNAs are vulnerable to enzymatic digestion, easily eliminated by renal filtration, and unable to cross the cell membrane due to their large, anionic structure. Therefore, effective delivery systems are required to protect siRNAs and maintain their functionality. In this review, we have discussed the promises of siRNA therapy in treating HBV, milestones in their delivery systems, and products that have entered clinical trials. Finally, we have outlined the future perspectives of siRNA-based therapy for HBV treatment. Graphical Abstract